Case Series of Skull Base Meningioma Resection in the Octogenarian Population - Kusyk, Dorian M.; Mao, Gordon; Dabecco, Rocco; Yu, Alexander K. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction The geriatric population is the fastest growing segment of the American population, and octogenarians are increasingly seen by neurosurgeons for relatively common lesions such as meningiomas. Unfortunately, providers do not have clear data to guide decision-making regarding these lesions, particularly if they involve the skull base. Current research in outcomes among the elderly looks at a wide range of ages, often anyone older than 65. Previous studies in octogenarians report a wide-range of mortality rates and do not focus on skull base lesions. This paper strives to clarify the experiences and outcomes of octogenarians.Patients and Methods This retrospective series reviews skull base tumor surgeries performed at a single academic institution over the past 15 years in octogenarian patients. Primary endpoint was 30-day mortality; however, potential risk factors, perioperative morbidity, postdischarge disposition, and longer term follow-up were also captured. Multivariate logistic regression was performed to identify relevant perioperative and medical characteristics that increases the risk of adverse events.Results Fourteen patients underwent craniotomies for skull base procedures with an average age of 84.5, with a 14% 30-day mortality rate. One patient required a tracheostomy on discharge and approximately half were able to either go home or rehabilitation after their procedure. On statistical analysis, there were no noted characteristics that predisposed any of the patients to a poorer outcome.Conclusion Octogenarian patients were able to tolerate surgery for skull base meningiomas resection. This outcome data may be used to inform surgical decision and guide conversation with patients and their families.
Keywords: skull base; meningiomas; octogenarian; geriatric neurosurgery